Sektor Basis dan Penyerapan Tenaga Kerja di Kota Sungai Penuh - Rahayu, Silvia; Yadewani, Dorris (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to identify the dominant base sectors in Sungai Banyak City and evaluate the level of labor absorption in these sectors. The data used comes from secondary sources, namely the websites of BPS Sungai Banyak City and BPS Jambi Province. The data analysis method involves a qualitative descriptive approach and quantitative descriptive analysis. The data collection period is 2018-2022. The analytical instrument applied involves Location Quotient (LQ) and labor absorption in the base sector. The research results show that there are four significant basic sectors in Sungai Banyak City in the 2018-2022 period. These sectors include Mining and Quarrying (LQ 1.11), Agriculture, Forestry and Fisheries (LQ 1.31), Construction (LQ 1.31), and Wholesale and Retail Trade (LQ 1.95). The highest labor absorption will occur in the Agriculture, Forestry and Fisheries sectors in 2022, with a total of 44,428 people. Meanwhile, the Wholesale and Retail Trade sector will absorb the largest number of workers in 2022, amounting to 15,013 people. The Mining and Construction sector, which is included in the other sectors category, accounts for 12,480 people in 2022.